The Spring security architecture for authentication and authorization - Spilcă, Laurenţiu (Manning Publications, 2020)
An experienced Java developer and technology teacher Laurentiu Spilca demonstrates how to use OAuth2 for authentication and authorization, as well as how to properly implement internet security.